Analisis Kebergunaan Aplikasi Sistem Informasi Manajemen Bank Sampah (SIMBA) pada Dinas Lingkungan Hidup Menggunakan Metode Webqual 4.0 - Lisa Ria Fitriani; Saikin Saikin (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
The development of information technology has encouraged government agencies to adopt digital systems to improve the quality of public services. One of these innovations is the Waste Bank Management Information System application (SIMBA), which is used by the Lombok Tengah Environment Agency. This research aims to analyze the usability of the SIMBA application based on three main dimensions of the Webqual 4.0 method, namely usability, information quality, and service interaction quality. The method used is a quantitative approach through the distribution of questionnaires to 51 respondents who are users of the application. Each dimension is measured using a five-point Likert scale to obtain users' perceptions of the quality of the application. The results of the study show that the score for the usability dimension is 188, information quality is 192, and service interaction is 188, with a total Webqual score of 189. This score falls into the 'good' category, indicating that the SIMBA application has met user needs in terms of usability, information quality, and service interaction quality. This research is expected to serve as an evaluation material for the development of environmental service information systems in the future.